Genomic medicine in the schools of Medicine of Peru: Medicina genómica en las escuelas de Medicina del Perú - Ñique-Carbajal, César (2020)
Nowadays genomic medicine plays an important role in the promotion of population health, this is defined as the use of genomic information and technologies to determine the risk, predisposition, diagnosis and prognosis of diseases, with a personalized approach to The therapeutic options It is definitely the use of a patient's genotypic information for the benefit of their clinical care. In Peru, there are few institutions that are adequately equipped and implemented to develop both genetics and genomics activities applied to medical practice, the efforts that are being carried out are on specific topics and in an unsustainable way. These topics include neurological diseases, hereditary cancer, pharmacogenetics and some pediatric issues. Likewise, Peruvian research in these areas emerges at a slow pace, with representative institutions that are outlined in this topic, among which we can mention: Center for Genetics and Molecular Biology Research of the San Martín de Porres University, the Research Laboratories and Development of Science and Technology of the Peruvian University Cayetano Heredia, the Institute of Research in Biomedical Sciences of the Ricardo Palma University, also as part of the health care sector highlights the work of the National Institute of Neoplastic Diseases, the National Institute of Child Health and the National Institute of Health. However, it is necessary to join efforts to be able to articulate and / or coordinate between institutions to carry out larger research.